INFLUENCE OF COPPER SULPHATE ON GLYCOGEN AND TOTAL LIPID LEVELS IN GILL AND KIDNEYS OF FISH, Oreochromis mossambicus (PETERS) - JAGADESHWARLU, R.; DEVI, G. SUNITHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Freshwater organisms face the challenge of being exposed to an assemblage of chemicals emitted by human activates. Thus, several biochemical parameters in fish organs could be used as indicators of heavy metal toxicity. In this study, Oreochromis mossambicus fish were exposed to sublethal concentrations (1/16, 1/12, 1/8 and 1/4th of 96 hours LC50 value), i.e. 3 mg/L, 4 mg/L, 6 mg/L and 12 mg/L of Copper Sulphate for different exposure periods of 10, 20, 30 and 40 days. The Glycogen level and Lipid level in the gills and kidneys were determined. The decreased Glycogen level and Lipid level in the two different organs of fish exposed to Copper Sulphate were observed when compared to control. Glycogen level and Lipid levels gradually decreased with increased exposure period, and the decrease was found to be directly proportional to increased sublethal concentrations. Thus it is concluded that the usage of Copper Sulphate must be reduced and to create an awareness among the people about the toxicity of CuSO4 on animals & humans.